Processual analysis of management to change: study at an educational institution - Vera L. Cançado; Juvêncio Braga de Lima; Aline Soares Amaral Baeta Mendonça (Revista Eletrônica de Ciência Administrativa, 2024)
This paper aimed to analyze how agents – managers and employees – experienced change in an educational institution, due to the Covid-19 pandemic. We developed a framework that considers the junction between Badham's 5M Framework (mindful, mobilising, mapping, mask, and mirror) and Pettigrew's processual approach to strategic change (why change - context, what to change – content, and how to change - process). We carried out a qualitative, descriptive, and explanatory case study in an educational institution, here called Beta. Data were collected through 12 narrative interviews with Beta’s managers and employees. And  they were analyzed by means of categorial content analysis technique, using the NVivo Software. The results revealed that the change occurred in three phases – the closure and online teaching; the hybrid teaching model; and the return to the ‘new normal’. To face the challenges, complexity and chaos, the unity and cohesion of the group to overcome a 'common enemy' - the pandemic - was preponderant. The sharing of solutions as well as the pain and suffering was built in a creative and flexible way, tuning the difficulties faced with support, counseling, and leadership strategies. This study allowed the elaboration of a theoretical framework that join the two approaches, called Processual Analysis of Management to Change.